THE EFFECTIVENESS OF VIRTUAL REALITY IN VOCATIONAL EDUCATION FOR FASHION DESIGN AND PRODUCTION - Irmayanti Irmayanti; Syahroni Hidayat; Heri Tri Luqman Budisantoso; Ahmad Mustamil Khoiron; Taofan Ali Achmadi (JURNAL EDUSCIENCE, 2026)
Purpose – The fashion industry must master the practical skills needed today to employ immersive technology like VR in Vocational Education and Training. Due to the cost and hazard of hands-on instruction, Indonesian vocational high schools have a skill gap. In order to deal with this problem, this study talks about the real-life outcomes of "Fashion Tech Edu-VR," an immersive learning tool that fits perfectly with the Indonesian national curriculum.Methodology – This study employs a quasi-experimental research approach with a pre-test and post-test Control Group Design. The research subjects consist of 90 grade XI (Phase F) students from the Fashion Design and Production expertise program at a Vocational High School (SMK) in Semarang City. The data collection techniques used were threefold: tests, observation, and questionnaires. To test the hypotheses in this study, a t-test (paired sample t-test) was utilized with the assistance of IBM SPSS Statistics 26, comparing the post-test scores between the control group and the experimental group.Findings – The findings show a statistically significant difference in learning outcomes between the control and experimental classes (t = -27.935). Student engagement in the control group was 3.31, compared to 4.62 in the experimental class after the Fashion Tech Edu-VR intervention. This study found that students who used 'Fashion Tech Edu-VR' achieved significantly higher learning gains compared to the control group. The platform also received excellent usability ratings and fostered much higher levels of student engagement, confirming its effectiveness as an educational tool.Contribution – The study concludes that "Fashion Tech Edu-VR" is a useful educational tool that solves real-world training problems and is a very effective teaching example